Peran Ayah Sebagai Pendidik Berdasarkan Efesus 6:4 - Tari, Ezra; Dimu, Maria Darniati; WEny, Nelman A. (SOPHIA: Jurnal Teologi dan Pendidikan Kristen, 2020)
This article attempts to discover the role of the father in the family. Today's job demands make fathers rarely at home and involved in education. There are even children who live without a biological father. This paper describes the importance of the role of fathers in the family. The investigation uses a phenomenological approach. This approach seeks to see phenomena in the field. Research shows that the father is an essential figure in the family. Not only as a breadwinner. Fathers have a responsibility that is to have a positive impact on children's behaviour. Moreover, a father understands his role in educating children.